Pengaruh Bauran Pemasaran terhadap Keputusan Konsumen Membeli Produk Hijau di Ubud Organic Market, Kecamatan Ubud, Kabupaten Gianyar - TRIAYUNI, LUH GEDE NANDA PRADNYAHERA; PARINING, NYOMAN; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.2, Juli 2020, 2020)
The Effect of Marketing Mix on Consumer Decisions to Buy Green Products in Ubud Organic Market, Ubud Sub-District, Gianyar Regency.  Public awareness about health and the environment has led to increased market demand for green products. Ubud Organic Market is a market that provides a variety of green products to meet market demand for green products. The purpose of this study was to determine the effect of the marketing mix on consumer decisions to buy green products and the most dominant variable in influencing consumers to buy green products in the Ubud Organic Market. The sampling technique was conducted by using purposive sampling with 42 respondents. The analysis technique used is descriptive analysis and SEM-PLS analysis with the help of the SmartPLS 3.0 program.The results of this study indicate that product and price variables respectively have a positive and significant effect onpurchasing decisions of green products, while place and promotion variables have a positive but not significant effect onpurchasing decisions of green products. Product variable has a dominant influence on consumers' decision to buy green products. Ubud Organic Market organizer advised to improved product quality sold. Management of similar green market needs to be considered because it can answer consumers desire to shop more than once at Ubud Organic Market . Promotion can be done in new ways to help spread information about the market.